Natural Resource Booms in the Modern Era : Is the curse still alive? - Warner, Andrew (IMF Working Papers; Working Paper ;, 2015)
The global boom in hydrocarbon, metal and mineral prices since the year 2000 created huge economic rents - rents which, once invested, were widely expected to promote productivity growth in other parts of the booming economies, creating a lasting legacy of the boom years. This paper asks whether this has happened. To properly address this question the empirical strategy must look behind the veil of the booming sector because that, by definition, will boom in a boom. So the paper considers new data on GDP per person outside of the resource sector. Despite having vast sums to invest, GDP growth per-capita outside of the booming sectors appears on average to have been no faster during the boom years than before. The paper finds no country in which (non-resource) growth per-person has been statisticallysignificantly higher during the boom years. In some Gulf states, oil rents have financed a migration-facilitated economic expansion with small or negative productivity gains. Overall, there is little evidence the booms have left behind the anticipated productivity transformation in the domestic economies. It appears that current policies are, overall, prooving insufficient to spur lasting development outside resource intensive sectors.